Partial coalescence in double (W 1 /O/W 2 ) emulsions prepared with skimmed milk, polyglycerol polyricinoleate, and different fats - Pérez, María Paula (2017)
Partial coalescence was studied in double (W1/O/W2) emulsions prepared with skimmed milk, polyglycerol polyricinoleate (PGPR) as lipophilic emulsifier, and different fats. Microstructural and rheological analyses were performed. Encapsulation efficiency (as a parameter of inner water retention) and solid fat content were estimated by differential scanning calorimetry. The presence of PGPR in dispersed lipid phase promoted partial coalescence especially at higher concentration. This promotion of partial coalescence may have been produced by the increase of collision frequency due to protein displacement by PGPR at the outer interface and/or the increase of capture efficiency due to the modification of fat crystals by PGPR. Partial coalescence was also favored when inner water droplets were released as a consequence of an osmotic unbalance between inner and outer aqueous phases. Thus, the addition of glucose in dispersed aqueous phase decreased the partial coalescence degree due to the higher encapsulation efficiency given by the balanced osmotic pressures. With respect to the effect of the employed fat on partial coalescence, the obtained data indicate that the phenomenon was favored at higher solid fat content in lipid phase. Results led to the conclusion that inner osmolality, encapsulation efficiency, and inhibition of partial coalescence were correlated.